ANALYSIS OF GEOGRAPHICAL TERMS - Abdurahmonov Adxamjon Sultonboevich; D. B. Olimjonov; S. F. Shamsiddinov; M. Zikriyoxujaeva (Journals Park Publishing, 2022)
The article deals with the interpretation of widespread geographical terms in the Ferghana Valley. In the case of these local terms, it is clear that they are diverse and participate in the formation of toponyms.
Keywords: geographical terms; adir; toponomics